TGF-beta/BMP system in experimental and idiopathic pulmonary hypertension - Amarie, Oana Veronica; Justus Liebig University Giessen (My University, 2009)
Pulmonary arterial hypertension (PAH) is a devastating disease, with an annual incidence of 1-2 patients per 106 population. Clinically, it is characterized by a sustained elevation of the mean pulmonary arterial pressure of more than 25 mmHg at rest and more than 30 mmHg during exercise, while in the healthy human it is ranging between 12 and 16 mmHg. Although the disease may occur at any age, PAH is usually diagnosed in the 4th decade of life, with a female-to-male ratio of 1.7:1, but in children the ratio between genders is almost equal. PAH occurs as an idiopathic disease (called idiopathic PAH, iPAH) and as a consequence of other illnesses, including connective tissue diseases, portal hypertension, diet and stimulant drug use, human immunodeficiency virus (HIV) infection, and congenital heart disease. Pulmonary arterial hypertension also occurs as a familial form, which is almost always due to mutations in genes of the transforming growth factor (TGF)-ß superfamily of receptors. The most common mutation leading to PAH is in the gene encoding bone morphogenetic protein receptor type II (BMPR-2), which was originally discovered to be involved in bone healing. Recent studies on the TGF-ß signalling pathway have reported mutations in the activin receptor-like kinase 1 (ALK1) gene, which belongs to the same family of receptors, with a mechanism similar to that of BMPR-2. The reported mutations have been observed in patients with hereditary hemorrhagic telangiectasia (HHT) in association with PAH. Evidence is emerging that imbalanced activation of other TGF-ß receptors may increase the likelihood of the development of PAH. Many signaling pathways have been found to participate in PAH, including K channels, serotonin, angiopoietin, and cyclooxygenases. The interaction of these signaling systems with the TGF-ß system, is currently a focus of research in PAH. Approaches to altering the imbalance in activation of BMPR-2, ALK1 and other TGF-ß; receptors may yield future therapies for PAH.Due to the complexity of the TGF-ß system and its documented causal role in PAH, we sought to analyze the expression and localization patterns of TGF-ß/BMP receptors and Smads in chronic hypoxia-induced pulmonary hypertension over time, as well as in the lungs of patients with iPAH. The expression of the TGF-ß/BMP receptors in the mouse model of hypoxia-induced pulmonary hypertension revealed decreased expression of ALK1, ALK3 and TGFß-R2 mRNA level in lungs of animals exposed to hypoxia for three weeks, compared with normoxia-treated controls, and no change in BMPR-2 mRNA levels. Among the pathway mediators, only Smad7 and Smad8 were downregulated at mRNA level after three weeks of hypoxia. The protein expression of ALK1, TGFß-R2, Smad1 and Smad4 was significantly downregulated after three weeks at hypoxia exposure. The localization of these molecules was then assessed, and staining for these molecules was observed in the bronchial epithelial cells and pulmonary arterial smooth muscle cells (PASMC), and in the heart muscle cells surrounding intrapulmonary veins. These changes were limited to the animal model of hypoxia-induced pulmonary hypertension, as not all changes in expression were observed in lungs from iPAH patients, with the exception of ALK1, which was downregulated in iPAH patients. Activin receptor like kinase 1 (ALK1), is well described to be expressed and active in endothelial cells (EC), however the expression of this receptor in smooth muscle cells represents a novel aspect of this work, and an attractive novel pathophysiological area and research subject on smooth muscle cell proliferation in PAH.

Pulmonalarterielle Hypertonie (PAH) ist eine verheerende Krankheit mit einer Inzidenz von 1 2 Patienten pro 106 Einwohner. Das klinische Bild ist durch einen ständig wechselnden Lungengefäßhochdruck gekennzeichnet, der definitionsgemäß in Ruhe über 25 mmHg beträgt und unter Belastung über 30 mmHg liegt. Obwohl diese Erkrankung in jedem Alter auftreten kann, wird sie am häufigsten in der vierte Lebensdekade diagnostiziert. Das Verhältnis weiblich zu männlich beträgt 1,7:1. Bei Kindern sind jedoch beide Geschlechter gleich stark betroffen. PAH ist meist eine idiopathische Erkrankung (idiopathische PAH, iPAH). Auch können einer PAH unter anderem Lungengewebserkrankungen, portale Hypertension, nutritive Ursachen, stimulierende Drogen, AIDS und kongenitale Herzerkrankungen zugrunde liegen. Beschrieben sind auch familiäre Formen der PAH, die auf Genmutationen innerhalb der Familie der transformierenden Wachstumsfaktorrezeptoren (TGF-ß) zurückzuführen sind. Häufig ist eine Mutation des Knochen-morphogenetischen Proteinrezeptortyp II (BMPR-2). Dieser wurde ursprünglich in der Knochenheilung entdeckt. Neuere Studien zur Signaltransduktion haben Genmutationen der Activin Rezeptor like Kinase 1 beschrieben, die zur gleichen Rezeptorfamilie zählt und einen ähnlichen Mechanismus wie BMPR-2 aufweist. Die beobachteten Mutationen wurden auch in Patienten mit einer hereditären haemorrhagischen Teleangiektasie (HHT) in Assoziation mit einer PAH beschrieben. Diese Befunde sprechen für einen Zusammenhang zwischen einer aktivierenden Dysregulation anderer TGF-ß Rezeptoren und der Entstehung einer PAH. Viele Faktoren in der Entstehung der PAH wie Kaliumkanäle, Serotonin, Angiopoetin und Cyclooxygenase wurden untersucht. Die Interaktion dieser Faktoren mit den TGF-ß Signalkaskaden steht gegenwärtig im Mittelpunkt des wissenschaftlichen Interesses verschiedener Arbeitsgruppen. Möglichkeiten die die Aktivität von BMPR-2, ALK-1 oder TGF-ß Rezeptoren beeinflussen bieten eventuelle zukünftige Therapieoptionen der PAH. Aufgrund der Komplexität des TGF-ß Systems und seiner dokumentierten ursächlichen Rolle in der PAH, haben wir dessen Expression in Verbindung mit der Morphologie des TGF-ß/BMP Rezeptors und Smads in Lungen mit einer Hypoxie-induzierten chronischen Pulmonalarterieller Hypertonie von Mäusen, sowie in explantierten Lungen von Patienten mit einer iPAH untersucht. Die Mäuselungen zeigten eine verminderte Expression von der ALK1, ALK3 und TGFß-R2 mRNA nach drei Wochen Hypoxie, verglichen mit Normoxie behandelten Mäusen, die keine Änderung der BMPR-2 mRNA Expression aufwiesen. Unter den Signaltransduktoren wiesen nach drei Wochen Hypoxie nur Smad 7 und Smad 8 eine herunterregulierte mRNA Expression auf. Nach drei Wochen Hypoxie fand sich eine signifikant herunterregulierte Proteinexpression von ALK1, TGFß-R2, Smad1 und Smad4. Die Lokalisation der Moleküle wurde mit der Methode der Immunhistologie detektiert. Die genannten Moleküle wurden in Bronchusepithelien, glatten Muskelzellen von Lungenarterien sowie venösen Lungengefäße beobachtet. Die Veränderungen konnten mit der Ausnahme von ALK1 nur im Tiermodell mit Hypoxie-induzierter PAH nachgewiesen werden. In iPAH Patienten wurde auch eine Herunterregulation von ALK1 festgestellt. Eine ALK1-Expression in aktivierten Endothelzellen ist allgemein bekannt. Ein neuer Aspekt dieser Arbeit ist die ALK1 Expression in glatten Muskelzellen der Gefäße, die möglicherweise in einem kausalen Zusammenhang mit den in einer PAH häufig beobachteten starken Proliferation von glatten Muskelzellen steht.
TGF-beta/BMP System in der experimentellen und idiopathische Lungenhypertonie
Keywords: TGF-beta; BMP; Pulmonalarterielle Hypertonie; ALK1; Hypoxie; glatten Muskelzellen; Proliferation; TGF-beta; BMP; pulmonary hypertension; ALK1; hypoxia; smooth muscle cells; proliferation; ddc:610